2014
DOI: 10.2478/s11534-014-0437-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of methicillin resistant Staphylococcus aureus by a plasma needle

Abstract: Abstract:In numerous recent papers plasma chemistry of non equilibrium plasma sources operating at atmospheric pressure has been linked to plasma medical effects including sterilization. In this paper we present a study of the effectiveness of an atmospheric pressure plasma source, known as plasma needle, in inhibition of the growth of biofilm produced by methicillin resistant Staphylococcus aureus (MRSA). Even at the lowest powers the biofilms formed by inoculi of MRSA of 10 4 and 10 5 CFU have been strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Total inhibition of biofilm formation (a 5 log decrease in CFU/ml) was achieved either by 2-min treatment with NTP produced at 0.9 W or only a 1-min exposure to NTP formed at 1.6 W. Different power regimes for NTP formation were also used in Modic et al (2017). The NTP used in this study achieved total inhibition (6.5 log decrease) of biofilm formation on coupons after 2 min at both working powers (8 and 34.5 W), similarly to Miletić et al (2014). Cotter et al (2011) studied the effect of NTP on S. aureus biofilms formed on coverslips.…”
Section: Biofilmmentioning
confidence: 83%
See 1 more Smart Citation
“…Total inhibition of biofilm formation (a 5 log decrease in CFU/ml) was achieved either by 2-min treatment with NTP produced at 0.9 W or only a 1-min exposure to NTP formed at 1.6 W. Different power regimes for NTP formation were also used in Modic et al (2017). The NTP used in this study achieved total inhibition (6.5 log decrease) of biofilm formation on coupons after 2 min at both working powers (8 and 34.5 W), similarly to Miletić et al (2014). Cotter et al (2011) studied the effect of NTP on S. aureus biofilms formed on coverslips.…”
Section: Biofilmmentioning
confidence: 83%
“…The occurrence of biofilm-related S. aureus infection is very common, so it is not surprising that NTP is primarily used to eradicate such contamination or to prevent surface biofilm formation. Miletić et al (2014) focused on the treatment of cell suspension before the biofilm formation in polystyrene microtiter plates using NTP discharge working at two power settings. Total inhibition of biofilm formation (a 5 log decrease in CFU/ml) was achieved either by 2-min treatment with NTP produced at 0.9 W or only a 1-min exposure to NTP formed at 1.6 W. Different power regimes for NTP formation were also used in Modic et al (2017) .…”
Section: Non-thermal Plasma Treatment Of Eskape Pathogensmentioning
confidence: 99%
“…Sharma et al [ 35 ] analyzed the influence of feeding gas flow rate in bacterial inactivation using Argon (Ar) and Helium (He) gas, and they noticed a decrease in the pathogen inactivation with the increased Ar gas flow; however, the observation was upturned while using He as the feeding gas [ 35 ]. The power and frequency have also a significant effect on pathogen inactivation; the inactivation efficiency of LTP increases with the increase in the input frequency and (or) power [ 36 , 37 ]. Studies with S. aureus show the bacterial inactivation efficiency of LTP by varying voltage.…”
Section: Introduction Low-temperature Plasma On Medicinementioning
confidence: 99%
“…In addition, these bacteria tend to 51 form biofilms where bacteria are well protected from 52 the outside agents. It has been shown that plasmas may sterilize even the biofilms as well as planktonic samples 54 [22].…”
Section: Introductionmentioning
confidence: 99%